Growth Performance of Twelve New Clones of Populus deltoides in Punjab, India - Luna, R. K.; Thakur, N. S.; Kumar, Vijay (Indian Forester, 2012)
Height, diameter growth and volume production of 12 clones of poplar were evaluated at Kharkan Research Station Hoshiarpur, Research Circle Hoshiarpur, Punjab Forest Department at the age of 3 years. The results of evaluation revealed that among the poplar clones under study, the clone WSL - 39 achieved the best growth and maximum volume production, attaining diameter of 14.74 cm; height 14.42 m and volume 0.1040 m3/tree at the age of 3 years. The clone WSL-39 outperformed for growth and volume since the beginning. However, the volume production of clone Udai was at par with WSL - 39 at 2 and 3 years of age. On the basis of present results WSL-39 and Udai clones can be included for plantation to broaden the genetic base and more importantly for productivity enhancement.